Giant solitary fibrous tumor pleura: Clinical dilemma and diagnosis - Amulyajit Kaur; Satyajit Singh Gill; Jaswinder Singh; Amandeep Singh; Narayanan Subramaniam Mani (Lung India, 2012)
Solitary fibrous tumors in the lung are rare neoplasms with distinct clinicopathological and immunohistochemical features. We report a giant solitary fibrous tumor of the pleura in a young male which remained silent clinically till it assumed gigantic proportions. Histology and immunohistochemistry were classical of a solitary fibrous tumor. Inspite of its appalling size it proved to be benign in behavior. This case depicts the vulnerability of this lesion to a clinical bungle. The report highlights the significance of clinical suspicion of this rare neoplasm and reveals the diagnostic associations and procedures to avoid emperical therapy and delay in curative surgical treatment.